Concentration dependence of quaternary ammonium monomer on the design of high-performance bioactive composite for root caries restorations. Issue 8 (August 2020) - Balhaddad, Abdulrahman A.; Ibrahim, Maria S.; Weir, Michael D.; Xu, Hockin H.K.; Melo, Mary Anne S.
Abstract: Objectives: Dental plaque build-up on the cervical area adjacent to gingival margins is a trigger factor for secondary caries around restored root caries lesions. Dimethylaminohexadecyl methacrylate (DMAHDM) and amorphous calcium phosphate nanoparticles (NACP) impart anti-caries effect by reducing the bacterial growth and releasing high concentrations of calcium and phosphate ions, respectively. The present study explored the optimization and formulation of dental composite with increased concentration of DMAHDM combined with NACP and its effect on mechanical behavior and antibacterial response. Methods: DMAHDM was incorporated into dental composite formulation at 3% and 5% with 20% NACP fillers. Mechanical properties were assessed by flexural strength and elastic modulus. The cationic charge density of the samples was determined using fluorescein staining assay. A human saliva-derived microcosm biofilm model was used to assess antibacterial response via colony-forming units, metabolic activities, lactic acid production, and live/dead assay. Surface roughness was measured after 48 h-biofilm formation. Results: The viability of human saliva microcosm biofilms was DMAHDM concentration-dependent, where all the microbiological assays were substantially reduced in the presence of 5%DMAHDM. The increased DMAHDM concentration mirrors an increased surface charge density of composites by 8–12 folds and reduced the growth of cariogenic species by 2–5 log ( p  ≤ 0.05). Metabolic activity and lactic acid were reduced by 70–90% and 48–99%, respectively. Increasing DMAHDM concentration up to 5% and its association with NACP fillers did not adversely affect the mechanical properties. Significance: A highly potent antibiofilm bioactive composite for root caries restorations having DMAHDM-NACP could be flexibly tailored during formulation without detrimental outcome for mechanical function. The enhanced antibacterial performance of the novel bioactive composite has great potential to suppress the dental plaque build-up that triggers secondary caries around the restored root caries lesions.